2019
DOI: 10.1097/coc.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted Versus Open D2 Gastrectomy for Advanced Gastric Cancer in Highly Selective Patients

Abstract: Objectives: The feasibility and efficacy of laparoscopic-assisted D2 gastrectomy (LAD2G) for advanced gastric cancer (AGC) remain controversial. We conducted a prospective cohort study to provide a comprehensive comparison of LAD2G and open D2 gastrectomy (OD2G) for AGC. Materials and Methods: Between April 2016 and December 2017, patients with clinical stage T2-4aN0-3M0 gastric cancer were enrolled and assigned to either LAD2G or OD2G group. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We have observed that the risk of neuropsychiatric symptoms increases with age (Kato et al, 2016;Hwang et al, 2018;Honda et al, 2018;Huang et al, 2019;Shim et al, 2019). This can be explained by the reduced adaptability of older people to new hospital conditions and the form of stress response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have observed that the risk of neuropsychiatric symptoms increases with age (Kato et al, 2016;Hwang et al, 2018;Honda et al, 2018;Huang et al, 2019;Shim et al, 2019). This can be explained by the reduced adaptability of older people to new hospital conditions and the form of stress response.…”
Section: Discussionmentioning
confidence: 98%
“…Optimal analgesia and adaptation of pharmacotherapy to patient needs is very important in home and hospice treatment, and thus minimises the risk of emergency hospitalisation. This is very important because the severity of pain and anxiety is important determinants of quality of life (Hong & Tian, 2014;Huang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Clavien–Dindo classification system is currently the most definitive criterion internationally for evaluating the postoperative complications including gastric cancer [ 23 ]. This study provided the basis for preventing complications after radical gastrectomy by comparing the impact of two surgical methods on the severity of postoperative complications and analyzing the risk factors of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%